Human Infection with Avian Influenza A(H9N2) Virus, Cambodia, February 2021 - Samnang Um; Jurre Y. Siegers; Borann Sar; Savuth Chin; Sarika Patel; Seng Bunnary; Makara Hak; Sothy Sor; Oum Sokhen; Seng Heng; Darapheak Chau; Tum Sothyra; et al. (Emerging Infectious Diseases, 2021)
In February 2021, routine sentinel surveillance for influenza-like illness in Cambodia detected a human avian influenza A(H9N2) virus infection. Investigations identified no recent H9N2 virus infections in 43 close contacts. One chicken sample from the infected child’s house was positive for H9N2 virus and genetically similar to the human virus.